Environmentally friendly lead-free soldering materials based on rapidly solidified Al-Sn foil (microstructure and stability) - Gusakova, Olga V.; Skibinskaya, Hanna N.; Shulya, Yuliya M. (Journal of the Belarusian State University. Ecology, 2020)
The results of the microstructure of the foil of Al-Sn system alloys with an aluminum contend of up to 10 at. % obtained by ultrafast quenching from a melt at a melt cooling rate of 10 5 K/s. The foil of alloys of eutectic and near-eutectic compositions solidifies with the formation of a tin-based solid solution supersaturated with aluminum. Aluminum particles the size of which does not exceed 200 nm precipitate at the grains volume and at the grains boundaries at room temperature, as a result of the continuous decomposition of the solid solution. The microstructure of the Al – 94,2 аt. % Sn and Al – 90,7 аt. % Sn foil, in addition to, contains not only nanoscale Al inclusions but large ones whose size grows with distance from the surface of the foil adjacent to the mold. A rapidly solidified foil has a microcrystalline structure. The formation of twins is observed in the Al – 97,8 аt. % Sn и Al – 96,7 аt. % Sn foil. With an increase in Al concentration, the average grain size decreases, and the number of twins increases. Ageing of the foil at room temperature leads to an increase in the Al concentration at the grain boundaries in the eutectic and near- eutectic alloys and to the formation of whiskers in the foil of alloys with an Al concentration exceeding 3 at. %.
Keywords: aluminum; tin; rapid solidification; microstructure; stability